2021
DOI: 10.1002/agg2.20175
|View full text |Cite
|
Sign up to set email alerts
|

Cover crop influence on soil water dynamics for a corn–soybean rotation

Abstract: Crop production is reduced by insufficient and/or excess soil water, which can significantly decrease plant growth and development. Therefore, conservation management practices such as cover crops (CCs) are used to optimize soil water dynamics, since CCs can conserve soil water. The objective of this study was to determine the effects of CCs on soil water dynamics on a corn (Zea mays L.)-soybean [Glycine max (L.) Merr.] rotation at three soil depths over 3 yr. The study was conducted at the Chariton County Cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
(73 reference statements)
1
6
0
Order By: Relevance
“…For example, using continuously measured data, Basche et al (2016) have observed an improved soil water storage because of the winter CC in a corn-soybean cropping system as compared to no cover crop (NCC). Using soil moisture sensors to the depth of 30 cm, Rankoth et al (2021) also observed higher volumetric water content for soil that had winter CC as compared to the NCC system. Alfonso et al (2020) showed that evapotranspiration in soybean that followed CC was reduced, and water productivity was increased as compared to the NCC system.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…For example, using continuously measured data, Basche et al (2016) have observed an improved soil water storage because of the winter CC in a corn-soybean cropping system as compared to no cover crop (NCC). Using soil moisture sensors to the depth of 30 cm, Rankoth et al (2021) also observed higher volumetric water content for soil that had winter CC as compared to the NCC system. Alfonso et al (2020) showed that evapotranspiration in soybean that followed CC was reduced, and water productivity was increased as compared to the NCC system.…”
Section: Introductionmentioning
confidence: 80%
“…Using soil moisture sensors to the depth of 30 cm, Rankoth et al. (2021) also observed higher volumetric water content for soil that had winter CC as compared to the NCC system. Alfonso et al.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A study was conducted by [26] showed establishment of cover crops has been contributed to increase in aggregate stability by improving soil structure, decreasing bulk density, increasing the soil's water-holding capacity by increasing the total porosity and saturated hydraulic conductivity (Ksat) as well as increasing the proportion of medium and coarse pores in which water may move easily through the dispersive soil. Other study was carried out by [27] reported that one of the most important advantages of planting cover crops was to increases in the enzymatic and microbial activity of the soil which is an essential source of organic matter. This has a major role in the diversity of soil microorganisms and associated with increase in nitrogen fixation [27].…”
Section: Introductionmentioning
confidence: 99%
“…al. et al., 2019), crop yields (Abdalla et al., 2019), nutrient retention (Janegitz et al., 2017; Muhammad et al., 2019; Rimski‐Korsakov et al., 2015; Sharma et al., 2018; Weerasekara et al., 2017), and water quality and soil moisture conservation (Delgado & Gantzer, 2015; Rankoth et al., 2021). Findings indicate that perennial vegetation, biomass crops, ground cover, commodity crops, and soil parameters affected soil thermal properties.…”
Section: Introductionmentioning
confidence: 99%